Using cinematic gangsters, samurais and robots to teach economics through film. (3rd March 2022) - Vidal, Daniel Diaz; Beekman, Robert
The economics education literature has been showing significant signs of a push away from traditional lectures, 'chalk and talk', to more innovative and attractive pedagogies that are more effective and better suited for today's generation. This paper is another contribution to this literature as it invites the economics instructor to use films to teach economics. The paper presents several movies and a documentary with a list of associated economic theories and concepts that can be related to specific clips. The paper serves as an invitation to the reader to use these examples, with a hope that she/he will create and disseminate her/his own examples going forward.